(3GdMQjI GdfbGHjI ai GdbGfhf GdebGQf (B/ s - (3CMeO agei YHOGdhgGH eLGgO s; (3CMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3GdMQjI GdfbGHjI UGQJ ef GdMQjGJ GdCSGSjI ddEfSGf h bO JVefgG EYdGf GdeHGOF h GdMbhb GdCSGSjI ai GdYed SfI (B1998 (3h gi MQjI JeGQS Ydi GdeSJhi GdaQOi HeYfi CfgG JYWi dcd ehGWf JhGaQJ ajg GdTQhW GdbGfhfjI(B: (3GdMb ai Jchjf GdfbGHGJ Ch GdEfVeGe EdjgG Ch GdEfSMGH efgG h jJQJH Ydi GdMb GdaQOi ai Jchjf GdfbGHGJ Ch GdEfVeGe EdjgG; GdEfJbGd HGdMQjI GdfbGHjI ef fWGbgG GdaQOi Edi fWGb LeGYi(B: (3MjK jJQJH Ydi eeGQSI GdMb ai Jchjf GdfbGHGJ ehdO JfXje ELJeGYi Ph TNUjI eYfhjI dfbGHI eSJbdI Yf GdCaQGO Gdechfjf dgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B395-402s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdJLeY GdYeGdi s; (3GdMQjI GdfbGHjI s; (3GdfbGHGJ GdYeGdjI s; (3eHOC YOe GdeSGS HGdMb aj GdYeds; (3GdJUfja GdfbGHjs; (3eHOC GdGSJbdGd GdfbGHjs; (3eTQhY GdHQYjs; (3GdGYJQGa HGdMQjI GdfbGHjIs; (3aQfSGs; (3Tjdjs; (3HQjWGfjGs; (3Gdabg GdEfLdjRjs; (3GdGfJNGHs; (3GdGfVeGes; (3GdJaQZ GdfbGHjs; (3GdMUGfI ef GdaUds; (3GdeaGhVI GdLeGYjIs; (3GdGVQGHs; (3GdYhdeIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs